PENGELOLAAN SITUS PURA MAOSPAHIT TONJA DENPASAR DALAM UPAYA PELESTARIANNYA - Sri Sugandhini, Luh Putu (Humanis; Volume 1. No. 1. November 2012)
Based on the fact in a pattern of religious life and the lives of Balinese' social culture, archaeological site which locates in the area of Bali is still functionalized by the Balinese people, this is what causes the archaeological site in Bali categorized as a heritage which still alive. One of them is the Moaspahit Tonja temple site which locates in Denpasar city, Traditional Village of Tonja which on the inside has an archaeological remains from the Megalithic and classical period, and therefore should be properly managed to stay awake their sustainability.
Keywords: Site, management, preservation.